Vaginal deliveries in a tertiary centre: a current profile - Christe, D. M.; Tamilselvi, D.; Surya, S.; Shobha, S.; Ponnuraja, C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: A normal delivery is what every woman wishes to have. The objective of this study was to find out the maternal and neonatal outcome and background characteristics of women delivering vaginally in a tertiary care center in Chennai, South India. Methods: For this one-year study, with power above 80%, Parturition records were selected by computerized random numbers, for a calculated sample size. Salient demographic features such as age, residential background and religion were noted. Details of obstetric history, past and current, delivery and baby details and admission to NICU were analyzed. Acceptance of postpartum contraception was noted. Results: A total of 338 women delivered vaginally. Majority of 63%, were from urban background. Late referrals were 19.2% of women,38.5% women had antenatal complications. Primigravida were 49.7%. Nearly 91.4% of women delivered naturally. Previous pregnancy loss was noted in 14.8%. Term deliveries were in 72% of women, and 2.7% of women delivered twins. Average birth weight among primi was 2.5kg and in multi it was 2.8 kg. There were no maternal deaths. Perinatal deaths of 2.96%, of which 90% were preterm births, and all among babies with birth weight below 1.5 kg. Conclusions: The larger majority of 91.4% of women had natural vaginal delivery. Primigravida were 49.7%, and 63% were from urban background. Antenatal complications, obstetric, medical or other complications were noted in 38.5 % of women. Most often observed complications were Gestational hypertension, Gestational diabetes, and Hypothyroidism. NICU care was required for 18% of babies. Preterm births were16.6%. Perinatal deaths were seen in 2.96% of babies. There were no maternal deaths.